From screen to shopping cart: Pengaruh congruence, wishful identification, dan source credibility terhadap keputusan belanja pada live streaming shopping di Indonesia. - Abdul Rokhim (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2025)
This study explores how congruence, wishful identification, and source credibility shape consumer behavior in Indonesia’s rapidly evolving live streaming shopping ecosystem. Grounded in the Stimulus–Organism–Response (S–O–R) model, the research investigates how these external stimuli activate key psychological mechanisms—namely parasocial interaction and trust—that subsequently influence purchase intention and actual buying behavior. Using survey data from 502 active live commerce users across TikTok Live, Shopee Live, and Instagram Live, the findings reveal that wishful identification forms the strongest emotional pathway through intensified parasocial bonds; congruence enhances perceived authenticity and relevance; while source credibility firmly establishes cognitive trust. Together, these mechanisms orchestrate the transformation from “screen” to “shopping cart.” The study contributes theoretically by integrating media psychology with live commerce persuasion, and practically by offering strategies for brands, creators, and digital platforms seeking to optimize their live streaming commerce engagement.